2021
DOI: 10.2147/ppa.s295428
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Oral Rehydration Therapy Use During the Diarrheal Episode and Associated Factors Among Mothers of Under-Five Children Visiting Public Health Facilities in North Showa Zone, Oromia Region, Ethiopia

Abstract: Background Oral rehydration therapy reduces mortality and morbidity due to diarrheal diseases. However, Oral rehydration therapy remains to be underused worldwide and particularly in low-income countries. This study aims to assess the prevalence of oral rehydration therapy use during diarrheal episode and associated factors among mothers of under-five children visiting public health facilities in North Showa zone, Oromia region, Ethiopia. Methodology Institutional based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
(12 reference statements)
0
10
0
Order By: Relevance
“…The finding is supported by other studies. 15 , 16 , 24 , 27 29 The possible justification might be that educated mothers presume better about the complication of diarrheal disease and they may seek early health treatment during the episode of diarrhea. 30 32 This was a good opportunity for mothers to obtain health education from health professionals and give the appropriate treatment or medication, including ORS, to their sick children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The finding is supported by other studies. 15 , 16 , 24 , 27 29 The possible justification might be that educated mothers presume better about the complication of diarrheal disease and they may seek early health treatment during the episode of diarrhea. 30 32 This was a good opportunity for mothers to obtain health education from health professionals and give the appropriate treatment or medication, including ORS, to their sick children.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies conducted in Ethiopia found that maternal educational status, 15,16 monthly income, 15 previous experience, 15,17 perception of tooth eruption, 17,18 knowing the severe sign of dehydration, 18 seeking advice from health facilities, 15,17 and knowledge of oral rehydration therapy 15,17 have an association with ORS utilization. However, those studies were conducted in specific areas of Ethiopia and were not nationally representative.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Children whose mothers had postnatal care visits were more likely to undergo diarrhoea treatment than those whose mothers did not have postnatal care visits. Women who had frequent postnatal care visitations could have been educated on the importance of timely diarrhoea treatment, resulting in their increased likelihood of treating their childrens’ diarrhoea [ 31 , 32 ]. The study also found that children whose mothers believed that permission to go and get medical help for self was a big problem were more likely to access diarrhoea treatment compared with those whose mothers believed that permission to go and get medical for self was not a big problem.…”
Section: Discussionmentioning
confidence: 99%
“…In Sub-Saharan Africa, the cases remain high due to poor perception of primary caregivers' management of diarrhea especially mothers (10,11). Studies showed that positive mothers' attitudes towards homebased management of diarrhea (HBMD) range from 39-78% (12)(13)(14)(15)(16)(17)(18). Home-based uids include, a mixture of salt, sugar, and water, breast milk, Gruels (diluted mixtures of cooked cereals and water), soup, rice water.…”
Section: Introductionmentioning
confidence: 99%